Direct comparison of the aging and memory effects of magnetic nanoclusters and nanoparticles - Sankar, C. Raj; Vijayanand, S.; Verma, Seema; Joy, Pattayil Alias (Solid State Communications, 2007)
The magnetic characteristics of a dense magnetic nanoparticle system and a spin glass system consisting of magnetic nanoclusters are compared. Zero field cooled and field cooled magnetization measurements, including aging and memory experiments, of the nanoparticle and the magnetic cluster systems show similar characteristics, suggesting a common origin for the spin glass-type behavior of the magnetic nanoparticle and nanocluster systems. (C) 2006 Published by Elsevier Ltd.
Keywords: Magnetic nanoparticles; magnetic properties; spin glasses